2003
DOI: 10.1097/01.tp.0000080068.22576.3b
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for pediatric liver retransplantation from living donors

Abstract: Re-LDLT can save patients with a failing allograft. To achieve better results after Re-LDLT, further investigations are necessary to understand the factors leading to poor outcome after Re-LDLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
1
31
2
Order By: Relevance
“…Previous single center and multicenter studies have revealed patient survival at one yr after retransplantation from 47% to 82%. This is decidedly inferior to that reported for primary LT (1–14). Owing to the scarcity of donor organs, hepatic retransplantation especially in pediatrics has generated significant ethical discussion regarding maximization of hepatic donor utilization.…”
contrasting
confidence: 62%
“…Previous single center and multicenter studies have revealed patient survival at one yr after retransplantation from 47% to 82%. This is decidedly inferior to that reported for primary LT (1–14). Owing to the scarcity of donor organs, hepatic retransplantation especially in pediatrics has generated significant ethical discussion regarding maximization of hepatic donor utilization.…”
contrasting
confidence: 62%
“…In fact, at some centers, LDLTs are the preferred option for that age group (1). And while surgery per se has been associated with some risk and morbidity for the donors, LDLTs for pediatric recipients have been well accepted by the transplant community and general public (2,3). Adult-to-adult LDLTs, a newer and larger procedure, are gaining popularity.…”
Section: Introductionmentioning
confidence: 99%
“…19 Taking into consideration the recipient mortality rate of 54.4% observed in the present study, it is necessary to determine clear indications and limitations for revision living-donor liver transplant to avoid morbidity and mortality in potential living-donor candidates.…”
Section: Discussionmentioning
confidence: 90%